(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the effects of containers and substrates on the growth and quality of coffee seedlings in different cultivars. The experiment was conducted in the seedling production sector of Ifsuldeminas - Campus Inconfidentes, Inconfidentes /MG, in a randomized block design with three replications per treatment, with the parcels consisting of 30 plants. The factorial scheme was 2 x 2 x 5 and consisted of two containers, two types of substrates and five coffee cultivars. Seedling growth and quality parameters were evaluated. The results obtained allowed to verify that for the production of seedlings, the containers and substrates interfere in the growth of the coffee seedlings, presenting the seedlings in the tube container with better quality using the commercial substrate, being the cultivar Acauã and the cultivar Topázio 1190, produced in bags with commercial substrate with better results. By multivariate analysis, it was found that the highest growth of seedlings in height and smallest collection diameter was responsible for their lower quality. Therefore, it is concluded that the bag filled with commercial substrate, provided seedlings with greater growth. The tube, filled with commercial substrate, provided better quality seedlings; the cultivar that showed the greatest imbalance was Catuaí 144, in the sachet; the cultivars with the best IQD are Acauã using a tube on a commercial substrate and Topázio 1190 in the bag; the variable that contributed most to the IQD was the MSSR; the standard substrate limited root growth.